Rekonstruksi Undang-Undang Perbankan Untuk Mewujudkan Perlindungan Nasabah Penyimpan Yang Integratif Dan Berkepastian Hukum - Febrianto, Danu; Emirzon, Joni; Febrian, Febrian (Jurnal Hukum & Pembangunan, 2021)
Banks have an important role in economic development through their function by collecting funds from the public in the form of deposits and channeling them to the public in the form of credit in order to improve the standard of living of the people at large. Currently the banking business is regulated in Act Number 7 of 1992 concerning Banking as amended by Act Number 10 of 1998 (abbreviated as "Banking Act”). In a period of 20 years from 1998 to 2018, there have been developments in regulations relating to the depositors protection which are scattered in various laws and regulations in the economic sector. This condition creates a potential problem of legal uncertainty because the regulations related to the protection of depositors are carried out gradually and in various laws and regulations outside the Banking Act, causing potential inconsistencies with the provisions of the Banking Act. Therefore, it is necessary to reconstruct the Banking Act in order to synchronize with legal development and meet the needs of the community in order to create an integrated and legal certainty protection for depositors in banking sector